Stimulation simulation as an innovation in the field of scientific management - Burianyk, Grigorii M.; Efimova, Tatyana V. (Journal of the Belarusian State University. Sociology, 2019)
The article deals with the situation with the use of bibliometric data for the evaluation of scientific and scientific-pedagogical work. The history of the formation of scientometrics as a field of scientific knowledge is analyzed, the mechanism of formation of the Hirsch index is revealed. Expert opinions on the validity of this and other indices for direct evaluation of scientific activity are given, near and long-term prospects of deformation of Russian science are evaluated in terms of total use of bibliometric indicators for the evaluation of the activities of individual scientists and research teams.